Penerapan model pembelajaran kooperatif tipe think talk write (TTW) untuk meningkatkan keterampilan menyelesaikan soal cerita matematika peserta didik kelas V sekolah dasar - Isnaini Maysaroh Husniah; Riyadi Riyadi; Hadi Mulyono (Universitas Sebelas Maret, 2020)
Abstract. This research having a problem formulation of how the application of the TTW type of cooperative learning model can improve the skill of solving math stories problem for 5th grade students on elementary school in Surakarta in the 2019/2020 academic years. The purpose of this research was to improve the skills to solve mathematical story problems using the cooperative learning model of TTW type in the 5th students students on elementary school in Surakarta. This research uses a class action research method with two cycles, four meetings. Data sources used were secondary and primary data. Data collection techniques used were observation, interview, documentation and tests. The validity test used were source triangulation and technique triangulation. The analysis technique uses the model of miles and Huberman. To find out the initial conditions of the skills to solve mathematical story problems, a pre-action test was conducted. The classical completeness of the pretreatment test was 0%. The percentage increased in first cycle was 65%, then increased again in cycle II was 91%. Based on the results of the research, it can be concluded that the learning model of TTW type can improve the skills to solve mathematical story problems on 5th students of elementary school in Surakarta in the 2019/2020 academic years. This research is expected to be able to add scientific insights and as input for further researchersKeywords: mathematical story problem solving skills, cooperative learning models of think talk write (TTW) type, elementary school